Issues in information policy - Yurrow, Jane (US. Department of Commerce Washington DCUS, 1981)
Reviews legal and economic foundations of US domestic information policy highlighting the roles of the Federal Government in making, administering and enforcing information policy. Discusses issues regarding the intent and effectiveness of current policies about dissemination and access and examines information privacy policy. Considers the tension between individual liberties, proprietary interests and societal welfare in the context of policies about openness and restriction of information flows. Discusses economic policies relating to information distribution. Details laws and economic principles that impact on information markets, property rights and subsidies, and the management of information flows.